Electrical instabilities in organic semiconductors caused by trapped supercooled water - Gomes, Henrique L. (2015)
It is reported that the electrical instability known as bias stress is caused by the presence of trapped water in the organic layer. Experimental evidence as provided by the observation of an anomaly occurring systematically at around 200 K. This anomaly is observed in a variety of materials, independent of the deposition techniques and remarkably coincides with a known phase transition of supercooled water. Confined water does not crystallize at 273 K but forms a metastable liquid. This metastable water behaves electrically as a charge trap, which causes the instability. Below 200 K the water finally solidifies and the electrical traps disappear. (c) 2006 American Institute of Physics.